2018
DOI: 10.1155/2018/2368386
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Endogenous Modulatory Systems to TMS- and tDCS-Induced Analgesia: Evidence from PET Studies

Abstract: Chronic pain is an important public health issue. Moreover, its adequate management is still considered a major clinical problem, mainly due to its incredible complexity and still poorly understood pathophysiology. Recent scientific evidence coming from neuroimaging research, particularly functional magnetic resonance (fMRI) and positron emission tomography (PET) studies, indicates that chronic pain is associated with structural and functional changes in several brain structures that integrate antinociceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 129 publications
(148 reference statements)
0
19
0
3
Order By: Relevance
“…HF rTMS produces excitatory effects, and is thought to enhance synapse Study of ineffective treatment is labeled gray tDCS transcranial direct current stimulation plasticity by inducing long-term potentiation (LTP). In contrast, LF rTMS generates inhibitory effects, presumably through long-term depression (LTD) [23,79,80]. rTMS may induce multiple alterations related to LTD and LTP [63].…”
Section: Promotion Of Gaba Releasementioning
confidence: 99%
“…HF rTMS produces excitatory effects, and is thought to enhance synapse Study of ineffective treatment is labeled gray tDCS transcranial direct current stimulation plasticity by inducing long-term potentiation (LTP). In contrast, LF rTMS generates inhibitory effects, presumably through long-term depression (LTD) [23,79,80]. rTMS may induce multiple alterations related to LTD and LTP [63].…”
Section: Promotion Of Gaba Releasementioning
confidence: 99%
“…In chronic pain patients Transcranial Magnetic Stimulation (TMS) and electrical direct Transcranial Stimulation (dTCS) are efficaciously used to modulate the activity of pain-related circuits (Klein et al, 2015 ; Dos Santos et al, 2018 ; Meeker et al, 2020 ) together with vagal stimulation (Costa et al, 2019 ). Theoretically, imaginatively induced analgesia could influence cortical plasticity (Kleim and Jones, 2008 ) mimicking the effects of TMS and dTCS by suggestions aimed at modulating the activity of the pain matrix (Casiglia et al, 2020 ) and enhancing the action of descending antinociceptive pathways (Beltran Serrano et al, 2020 ).…”
Section: Cortical Plasticitymentioning
confidence: 99%
“…The precise mechanisms of action remain incompletely elucidated [15]. Recent studies using 3D-positron emission tomography have shown that rTMS applied to M1 for pain relief activates the endogenous opioid system in a wide brain network associated with processing of pain and other salient stimuli [25,26]. The stimulation frequency and type and orientation of the stimulating coil are considered as the most crucial variables to achieve a good response [22,27].…”
Section: Introductionmentioning
confidence: 99%